Lo que pueden decir de la comida chilena los diccionarios fundacionales. Primera parte. - CHÁVEZ FAJARDO, SOLEDAD (Scripta)
The purpose of this article is to present an ongoing investigation: to give an account of what is behind a lexicographical article related to the semantic field of food in the foundational Hispanic-American lexicography. The research has two objectives: to present a proposal for typologizing this information and to give an account of the functions that these lexicographical articles have. These functions will be two, which have to do with the normative role that these dictionaries had and, on the other hand, with the ethnographic role, with respect to showing, directly or indirectly, a Latin American reality.